Effect of intravenous magnesium on postoperative pain control for major abdominal surgery: a randomized double-blinded study - Arash Peivandi Yazdi; Mehrdad Esmaeeli; Mehryar Taghavi Gilani (Anesthesia and Pain Medicine, 2022)
Background This study aimed to evaluate the postoperative analgesic effect of magnesium sulfate during abdominal surgery. Methods This randomized double-blinded study involved 84 patients candidates for abdominal surgery into two same groups. In the magnesium group, at first 25 mg/kg/1 h magnesium sulfate; and then, 100 mg/kg/24 h was infused in the intensive care unit. The pain intensity (the primary outcome), was assessed using the numeric rating scale (NRS) every 3 h. If the NRS was > 3, morphine (as a secondary outcome) was used and evaluated. The results were analyzed using SPSS ver. 19 software, and statistical significance was set at P < 0.05 Results Demographic parameters were similar between the groups. The pain intensity were similar at first and then at the third hour in both groups (P = 0.393 and P = 0.172, respectively), but thereafter between 6 and 24 h, the pain severity was significantly lower in the magnesium group (4.4 ± 1.3 in the control and 3.34 ± 1 in the magnesium group at 6th hour and P = 0.001). In addition, morphine intake in the first 24 h in the two groups had a significant difference, with 13.2 ± 5.7 mg in control group and 8 ± 3.5 mg in magnesium group (P = 0.001). Conclusions In this study, intravenous magnesium sulfate after abdominal surgeries for 24 h resolved the pain intensity after six hours and reduced morphine dosage.